Computational investigation of diesel injection strategies in hydrogen-diesel dual fuel engine. (December 2019) - Tripathi, Gaurav; Sharma, Priybrat; Dhar, Atul; Sadiki, Amsini
Abstract: This paper deals with the numerical study of hydrogen-diesel dual fuel engine characteristics under various diesel injection strategies. Here, CONVERGE CFD software package is used to simulate a hydrogen diesel dual fuel engine, under split injection of diesel. The combustion and spray is modeled using coupled solution of chemical kinetics and fluid mechanics (CFD) equations. The study was performed at four strokes direct injection compression ignition engine. The engine speed (1500 rpm) and compression ratio (19.5:1) remain constant throughout the study. The developed model was validated against already published experimental data of 18.5% hydrogen energy share. The simulation result showed that 8° bTDC was optimum injection timing for single injection case and 16° bTDC was optimum injection timing for pilot fuel injection and 10% pilot mass was optimum pilot mass amount for minimum NOx, soot, CO and HC emissions and higher gIMEP.